An analysis of 11.3 million screening tests examining the association between needle biopsy rates and cancer detection rates in the English NHS Breast Cancer Screening Programme. Issue 5 (May 2019) - Blanks, R.G.; Given-Wilson, R.; Alison, R.; Jenkins, J.; Wallis, M.G.
Abstract : AIM: To examine the association between recall, needle biopsy, and cancer detection rates to inform the setting of target ranges to optimise the benefit to harm ratio of breast screening programmes. MATERIALS AND METHODS: Annual screening programme information from 2009/10 to 2015/16 for the 80 screening units of the English National Health Service Breast Screening Programme (totalling 11.3 million screening tests) was obtained from annual (KC62) returns. Linear regression models were used to examine the association between needle biopsy rates and recall rates and non-linear regression models to examine the association between cancer detection rates and needle biopsy rates. RESULTS: The models show and quantify the diminishing returns for prevalent screens with increasing biopsy rates. A biopsy rate increase from 10 to 20 per 1, 000 increases the cancer detection rate by 2.13 per 1, 000 with four extra biopsies per extra cancer detected. Increasing the biopsy rate from 40 to 50 per 1, 000, increases the cancer detection rate by only 0.25 per 1, 000, with 40 extra biopsies per extra cancer detected. Although diminishing returns are also seen at incident screens, screening is generally more efficient. CONCLUSIONS: Increasing needle biopsy rates leads to rapidly diminishing returns in cancer detection and a marked increase in non-malignant/benign needle biopsies. Much of the harms associated with screening in terms of false-positive recall rates and non-cancer biopsies occur at prevalent screens with much lower rates at incident screens. Needle biopsy rate targets should be considered together with recall rate targets to maximise benefit and minimise harm. Highlights: There is wide variation in needle biopsy rates in the English NHS breast screening programme. Increasing needle biopsy rates leads to a rapid increase in false positive needle biopsies. Needle biopsy rate target ranges should be considered along with recall rate target ranges.